PENANAMAN NILAI KARAKTER DALAM PEMBELAJARAN ANAK SD MELALUI CERITA RAKYAT SARIDIN - Sari, Syibilla Oktavia Malaka; Ulhaq, Jessica Dhiya'; Eka Putri, Hasna Dyah; Fatmasari, Diah; Rohmah, Nihayatur; Kanzunnudin, Mohammad (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2023)
The process of learning character education for elementary school children is an important thing in the world of education. Instilling character values ​​is not only in the family environment, but anywhere, for example at school. Children will know the character values ​​obtained through the learning process at school. This research was conducted with the aim of teaching character values ​​to elementary school students through the folklore